Political Economy of Modern Parenthood: Network Society and Social Capital - Жанна Владимировна Чернова; Лариса Леонидовна Шпаковская (Journal of Economic Sociology, 2011)
The article is devoted to a virtual community of parents functioning in the city of Saint-Petersburg. Based on a case-study, it considers the role of online communication in formation of parents’ social networks, principles on which their relationships are being built, ways of mutual support and channels for resource circulation, mechanisms and rules governing this circulation, contributions of parents’ community members to the organization of this private sphere. The paper demonstrates how production and accumulation of social capital are organized in the community; how reputations are evaluated by the participants; and how reciprocal exchanges of emotional support, information, goods and services are being arranged. The authors assume that participation in this online community produce new patterns for optimization of material, emotional and temporal resources of the family to maintain care and privacy. The analysis of these patterns has a good chance to contribute to the political economy of parenthood. In conclusion, authors show that social capital based on mutual aid and confidence among participants can be converted into economic capital and a resource for collective mobilization aimed to protect the rights of the virtual community members.